The Oxford handbook of religion and Europe - Davie, Grace (Oxford handbooks, 2022)
Religion and Classical Europe, 12th century BCE -- 600 CE /Christoph Auffarth --Christian Democracy and Europe /Kees van Kersbergen --Religion and the Cold War in Europe /Dianne Kirby --Religion and Europe after the Fall of the Iron Curtain /Lucian Turcescu, Lavinia Stan --Religion-State Relations in Europe /John T. S. Madeley --Religion, Secularity, and Secularisation in Europe /Grace Davie --Religion and Politics in the European Union /Lucian N. Leustean --Religion and Law in the European Union /Norman Doe, Frank Cranmer --Religion and the European Parliament /Fran cois Foret --Religion and the European External Action Service /Fran cois Foret --The Conference of European Churches /Peter Pavlovic --Religion and the Latin Western Europe, 600-1500 /Geoffrey Koziol --The Commission of the Bishops' Conferences of the European Community: COMECE /Frank Turner SJ --Religion and the Organization for Security and Cooperation in Europe /W. Cole Durham Jr. --Religion, Belie,f and the European Court of Human Rights /Peter Cumper, Tom Lewis --Religion and the United Nations /Jeffrey Haynes --Roman Catholicism and Europe /Petr Kratochv il --Protestantism and Europe /Brent F. Nelsen, James L. Guth --Eastern Orthodoxy and Europe /Effie Fokas --Islam and Europe /Jocelyne Cesari --Judaism and Europe /Miri Freud-Kandel --Eastern Religions and Europe /Martin Baumann --Religion and the Orthodox Commonwealth, 700-1500 /Matthew C. Briel --Nonreligion and Europe /Josh Bullock, Stephen Bullivant --Managing Religious Diversity in Europe /Thomas Sealy, Tina Magazzini, Tariq Modood, Anna Triandafyllidou --The Baltic countries /Sebastian Rimestad --Central Europe /Arp ad von Klim o --France /Blandine Chelini-Pont --Germany /Michael Minkenberg --Ireland and the United Kingdom /Gladys Ganiel, Martin Steven --Italy /Claudio Ferlan, Marco Ventura --The Low Countries /Arie L. Molendijk --Nordic Europe /Inger Furseth --Judaism, Christianity, and Islam in Medieval Europe /Ryan Szpiech --Ukraine and Russia /Heather J. Coleman --Southeast Europe /Vasilios N. Makrides --Spain and Portugal /Julio de la Cueva --Turkey /Ceren Ozg ul --Peripheries /Grace Davie, Ansgar J odicke, Vasilios N. Makrides --Religion and Europe: Methods, Theories, and Approaches /Grace Davie, Lucian N. Leustean --Reformation and Counter-Reformation in Europe /Jonathan Willis --The Enlightenment and Religion in Europe /Paschalis M. Kitromilides --Religion and Revolution in Europe /Bryan A. Banks, Erica Johnson Edwards --Religion and Nationality in Europe /Steven Grosby --Religion and Dictatorship in Europe /Richard Steigmann-Gall.